2013
DOI: 10.4274/tjh.2012.0135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Safety of Imatinib Mesylate in 200 Iraqi Patients with Chronic Myeloid Leukemia in the Chronic Phase: Single-Center Study

Abstract: Objective: Imatinib mesylate, a tyrosine kinase inhibitor, is presently the drug of choice for chronic myeloid leukemia (CML). During therapy, a few patients may develop hematological and non-hematological adverse effects. Materials and Methods: The aim of this study was to evaluate the safety of imatinib therapy in patients with CML. Between December 2007 and October 2009 two hundred patients with CML in chronic phase were included in the study. Written informed consent was obtained from all patients prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
2
4
0
1
Order By: Relevance
“…There was slight male predominance in this study which was concordant with the results of other Iraqi studies [16], [17], [22], and with Turkish results [19].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There was slight male predominance in this study which was concordant with the results of other Iraqi studies [16], [17], [22], and with Turkish results [19].…”
Section: Discussionsupporting
confidence: 93%
“…These results comparable to other Iraqi studies done in 2013 and 2012 [16], [17]. Similar results were also reported in Saudi Arabia study [18].…”
Section: Discussionsupporting
confidence: 92%
“…Sex, age, marital status, occupation and education level were similar between the cytopenia and no cytopenia groups and they did not increase the odds of developing cytopenia. A study carried out in Iraqi reported that females on imatinib had a predilection for anemia compared to males (20). This higher likelihood is probably due to the lower level of hemoglobin found in females at baseline compared to males (21).…”
Section: Discussionmentioning
confidence: 99%
“…Neutropenia developed in 33%, thrombocytopenia in 18%, and anemia in 6% of the patients [8]. In contrast, a study conducted in Indonesia reported lower levels of cytopenia with anemia at 20%, thrombocytopenia at 14%, and neutropenia at 4% [14] while a study from Iraqi documented anemia at 14%, and neutropenia and thrombocytopenia at 10% and 4% [15]. Lower proportions of cytopenia reported in some studies may be due to the analysis of patients with grade 3 and 4 cytopenia only.…”
Section: Discussionmentioning
confidence: 99%